PERANCANGAN WEBSITE CV. CIPTA CEMERLANG ABADI SEMARANG SEBAGAI MEDIA PROMOSI - Siswanto Siswanto; Muhammad Sidik (STEKOM PRESS, 2019)
Marketing or promotional strategies used by the Company CV. Cipta Cemerlang Abadi still uses banners posted in strategic places and distributed brochures. With the promotion media, Banners have problems that are often replaced or removed by others, because the installation of banners has not used official government tax. And for brochure media, there are constraints on increasing production costs to print and spread the promotional media. So most consumers who enter only those who often work with this company or customers. By utilizing the development of the Internet world, where there are millions of users and can be accessed anywhere and anytime, to promote the work of design and sales, the CV. Cipta Cemerlang Abadi doesn't need to bother going to and fro to put up banners and print brochure media. All can be done easily using an internet connection, consumers can see examples of design results or find the computer they want from a website. With a website, this company can distribute product marketing quickly and accurately. Another advantage is that consumers can interact with other consumers or with CV. Cipta Cemerlang Abadi directly.